THE EFFECT OF CURRENT RATIO, TOTAL ASSET TURNOVER, DEBT TO EQUITY, AND RETURN ON ASSETS ON PROFIT GROWTH OF FOOD AND BEVERAGES COMPANIES LISTED ON THE BEI FOR THE 2019-2020 PERIOD (BEFORE AND DURING THE COVID-19 PANDEMIC) - Purwandari, Emi; Ambarwati, Sri Dwi Ari; Pujiharjanto, Ambar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study is to analyze the effects of current ratio, total asset urnover, debt to equity ratio, return on assets, and the situational COVID-19 pandemic on the profit growth of food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2020 period. The purposive sampling technique was used to select the research sample and obtained a sample size of 23 food and beverage companies. Panel Data Regression Analysis with COVID-19 situational dummy variables is used as an analysis technique. The results showed that the current ratio has a negative effect on earnings growth and the debt-to-equity ratio has a positive effect on earnings growth. Total asset turnover and return on assets have no effect on earnings growth. Meanwhile, the COVID-19 situational dummy variable has a positive effect on the profit growth of food and beverage companies. Food and beverage companies should focus on efficient working capital management by reducing the amount of inventory, receivables, and debt outstanding, considering appropriate debt and equity policies, and analyzing risks and benefits. And identify and develop strategies to deal with the impact of the pandemic by expanding online distribution channels, providing delivery services, or optimizing production processes with COVID-19 safety protocols. Keywords: CR, DER, Profit Growth, ROA, TATO